Tricellulin is a target of the ubiquitin ligase Itch. Issue 1 (24th April 2017) - Jennek, Susanne; Mittag, Sonnhild; Reiche, Juliane; Westphal, Julie K.; Seelk, Stefanie; Dörfel, Max J.; Pfirrmann, Thorsten; Friedrich, Karlheinz; Schütz, Anja; Heinemann, Udo; Huber, Otmar
Abstract : Tricellulin, a member of the tight junction–associated MAGUK protein family, preferentially localizes to tricellular junctions in confluent polarized epithelial cell layers and is downregulated during the epithelial–mesenchymal transition. Posttranslational modifications are assumed to play critical roles in the process of downregulation of tricellulin at the protein level. Here, we report that the E3 ubiquitin ligase Itch forms a complex with tricellulin and thereby enhances its ubiquitination. Pull‐down assays confirmed a direct interaction between tricellulin and Itch, which is mediated by the Itch WW domain and the N‐terminus of tricellulin. Experiments in the presence of the proteasome inhibitor MG‐132 did not show major changes in the levels of ubiquitinated tricellulin in epithelial cells, suggesting that ubiquitination is not primarily involved in proteasomal degradation of tricellulin, but it appears to be important for endocytosis or recycling. In contrast, in HEK‐293 cells, MG‐132 caused polyubiquitination. Moreover, we observed that well‐differentiated RT‐112 and de‐differentiated Cal‐29 bladder cancer cells show an inverse expression of tricellulin and Itch. We postulate that ubiquitination is an important posttranslational modification involved in the determination of the intracellular fate of tricellulin deserving of more detailed further investigations into the underlying molecular mechanisms and their regulation.